An advanced and highly efficient Ce assisted NiFe-LDH electrocatalyst for overall water splitting. Issue 1 (30th October 2019) - Jadhav, Harsharaj S.; Roy, Animesh; Desalegan, Bezawit Z.; Seo, Jeong Gil
Abstract : A room-temperature synthesized NiFeCe2 electrocatalyst delivered a current density of 10 mA cm −2 at a cell voltage of 1.59 V when used as the electrolyzer. Abstract : Design and synthesis of highly catalytically active, low-cost, and stable electrocatalysts for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are the greatest challenges in electrochemical water splitting. In this work, we synthesized an efficient Ce-doped NiFe-layered double hydroxide (LDH) electrocatalyst directly on a nickel foam (NF) substrate at room temperature using an electrodeposition technique. A well-connected nanosheet array forming a three-dimensional (3D) network on the substrate provided a large electrochemical surface area with abundant catalytically active sites. Ce doping in the NiFe-LDH electrocatalyst was vital to enhancing its catalytic performance for the OER and HER. The optimized Ce-doped NiFe-LDH required overpotentials of 175 and 147 mV for the OER and HER, respectively, to achieve a current density of 10 mA cm −2 in 1 M KOH. The Ce-doped electrocatalyst outperformed bare NiFe-LDH, which required overpotentials of 197 and 175 mV for the OER and HER, respectively. However, when Ce-doped NiFe-LDH was used as a bifunctional catalyst for full water splitting, it needed only 1.59 V to achieve a current density of 10 mA cm −2 and exhibited excellent stability over 40 hours at 20 mA cm −2 . The enhanced electrochemical performance of Ce-doped NiFe-LDH was ascribed primarily to its unique 3D network, which increased the electrochemical surface area, and to the number of active sites created with Ce doping. The route used in the present study to enhance the catalytic activity of NiFe-LDH can be used to develop various electrocatalysts for water splitting and other catalytic applications.